A framework for improving the responsiveness of policy through development evaluation. (April 2016) - Porter, Stephen
Development evaluation, which prioritizes poverty reduction, potentially can increase the responsiveness of policy to poor people. Power imbalances, however, mean that although development evaluation has the possibility to be an important contributor to poverty reduction efforts, the interests of the poor are often excluded from the process of evaluation. In this article a framework that utilizes principal–agent concepts is detailed and applied, drawing on five case studies. An emerging configuration of principal–agent relations within the case studies is discussed and some potential entry points for evaluation to support responsiveness are highlighted. This discussion provides initial evidence of the applicability of the principal–agent concepts to advance development evaluation practice.